Respuesta :

[tex]\huge{ \mathfrak{ \underline{ Answer \: \: ✓ }}}[/tex]

The equations are :

-3x + 4y = 7. - [1]

2x + y = -1 - [2]

[tex] \underline{ \underline{ \bf{step} - 1}}[/tex]

multiply equation [2] with 4

[tex] \longrightarrow(2x + y = -1 ) \times 4[/tex]

[tex] \longrightarrow8x + 4y = - 4[/tex]

[tex] \underline{ \underline{ \bf{step} -2}}[/tex]

subtract equation [1] from [2]

[tex] \longrightarrow8x + 4y - ( - 3x + 4y) = - 4 - 7[/tex]

[tex] \longrightarrow8x + 4y + 3x - 4y = - 11[/tex]

[tex] \longrightarrow11x = - 11[/tex]

[tex] \longrightarrow \: x = - 1[/tex]

[tex] \underline{ \underline{ \bf{step} - 3}}[/tex]

plugging the value of x in equation [1]

[tex] \longrightarrow- 3x + 4y = 7[/tex]

[tex]\longrightarrow - (3 \times - 1) + 4y = 7[/tex]

[tex]\longrightarrow3 + 4y = 7[/tex]

[tex]\longrightarrow4y = 4[/tex]

[tex]\longrightarrow \: y = 1[/tex]

[tex] \#TeeNForeveR[/tex]

ACCESS MORE